Longevity of U cells of differentiated yeast colonies grown on respiratory medium depends on active glycolysis - Čáp, Michal; Váchová, Libuše; Palková, Zdena (Cell cycle (Georgetown, Tex.), 2015)
Colonies of Saccharomyces cerevisiae laboratory strains pass through specific developmental phases when growing on solid respiratory medium. During entry into the so-called alkali phase, in which ammonia signaling is initiated, 2 prominent cell types are formed within the colonies: U cells in upper colony regions, which have a longevity phenotype and activate the expression of a large number of metabolic genes, and L cells in lower regions, which die more quickly and exhibit a starvation phenotype. Here, we performed a detailed analysis of the activities of enzymes of central carbon metabolism in lysates of both cell types and determined several fermentation end products, showing that previously reported expression differences are reflected in the different enzymatic capabilities of each cell type. Hence, U cells, despite being grown on respiratory medium, behave as fermenting cells, whereas L cells rely on respiratory metabolism and possess active gluconeogenesis. Using a spectrum of different inhibitors, we showed that glycolysis is essential for the formation, and particularly, the survival of U cells. We also showed that β-1,3-glucans that are released from the cell walls of L cells are the most likely source of carbohydrates for U cells.
Keywords: Substrate Specificity; fermentation; kultivační média; Cell Wall; Microbiological Techniques; buněčná stěna; fenotyp; Serial Passage; Glycolysis; beta-glukany; Colony Count, Microbial; metabolic differentiation; enzymatic assays; respiration; mikrobiologické techniky; Saccharomyces cerevisiae Proteins; Phenotype; Genotype; Fermentation; sériové pasážování; Culture Media; počet mikrobiálních kolonií; glykolýza; substrátová specifita; Microbial Viability; Time Factors; Saccharomyces cerevisiae; genotyp; časové faktory; mikrobiální viabilita; Saccharomyces cerevisiae - proteiny; Enzyme Inhibitors; yeast colonies; inhibitory enzymů; beta-Glucans; fermentace